Does the Use of a Brief Cryotherapy Intervention With Analgesic Administration Improve Pain Management After Total Knee Arthroplasty?. (May 2015) - Wittig-Wells, Deborah; Johnson, Ifeya; Samms-McPherson, Jacqueline; Thankachan, Soosan; Titus, Bobina; Jacob, Ani; Higgins, Melinda
<x xml:space="preserve">Abstract</x> BACKGROUND: Prior studies have evaluated only the prolonged use of cryotherapy as a nonpharmacologic pain intervention. PURPOSE OF THE STUDY: The purpose of this study was to determine whether a 30-minute application of cryotherapy at the time pain medication was given after a total knee arthroplasty (TKA) provided better pain relief than analgesic drugs alone. METHODS: A pretest, posttest, randomized controlled trial study design with crossover was used to evaluate the effects of cryotherapy on postoperative pain and satisfaction with pain management. A convenience sample of postoperative knee replacement patients constituted participants in the study. Two sequential episodes of pain requiring analgesic administration were studied in each patient, one with a 30-minute cryotherapy application and the other without cryotherapy. Dependent variables were changes in pain (posttest minus pretest) and level of satisfaction with pain management. Data were analyzed with repeated-measures analysis of variance, with p < .05 considered significant. RESULTS: During two sequential treatments for postoperative pain, a total of 29 TKA patients received analgesic medication administration alone for one pain episode and analgesic medication administration with a brief cryotherapy administration for the other pain episode. No significant difference between the two treatments was found for changes in pain scores after the treatments or patient satisfaction with pain management (p > .05). The order in which the treatments were provided was found to be significant (p = .02) for scores on patient satisfaction with pain management, with cryotherapy as the treatment for the second pain episode having higher scores than when delivered for the first pain episode. Sixty minutes after analgesic administration with or without cryotherapy, average pain scores remained greater than 7. CONCLUSION: In TKA patients, the short-term application of cryotherapy with analgesic medication administration did not significantly decrease pain or improve patient satisfaction with pain management compared with analgesic medication administration only. Further study is necessary to determine whether short-term cryotherapy shortly after TKA is of benefit to pain relief and patient satisfaction.